Long walk to semi-freedom: Towards a framework for psychological research on being out on bail - Mbatha, Khonzi; Terre Blanche, Martin (PINS-Psychology in Society, 2018)
An important focus for psychological and other research on the criminal justice system concerns people who have been charged and are awaiting trial. However, most of this research has thus far focussed on remand detainees, who make up almost a third of the South African prison population. In this article we focus instead on those who are not in detention, but out on bail. Given the dearth of psychological research on bail we present a framework for researching the bail experience, incorporating both individual and community psychology perspectives. We identify five key elements in how individuals may experience being out on bail, namely, relief, uncertainty, identity issues, struggles related to belief in a just world, and being compelled to tell a “thin story”. Each of these elements is associated with particular possibilities for future research. From a community psychological perspective, we identify two key characteristics of the “bail community”, namely that it is firstly a ‘community of disconnection’ and secondly a “community of transience” – each of which, again, provides important research opportunities. It is our hope that this model will aid in directing and framing future research on the psychology of bail.